Words and Politics: Interweaving, Discrepancies, Perspectives - Alessandra Augelli (University of Bologna, 2020)
The birth and development of the social networks and media have brought about significant changes in communication, not only at the level of private and intimate relationships but also in community relations. The current political debate has been greatly affected by these transformations, and at the same time - by interweaving the spread of populism - it risks constantly manipulating reality and bending it to personal and party interests, behind an apparent process of democratic expression. The article aims to develop a pedagogical view on the topic of political communication, highlighting the interweaving between the use of speech and the shaping of civic consciousness, addressing issues related to the distortion of language, the increase of words of hatred, fake information. In addition, an attempt is made at tracing out some educational perspectives to improve communicative style in politics, exemplifying some directions of meaning.